2002
DOI: 10.1145/502269.502298
|View full text |Cite
|
Sign up to set email alerts
|

Constructive approaches to internet recreation in the workplace

Abstract: "Banana Time" takes on new dimensions when it comes to the Internet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 3 publications
6
43
0
7
Order By: Relevance
“…One nationwide study in the United States found that fully 80% of computer-using employees report using the internet for personal use on the job (Garrett & Danziger, 2008). Such employees report that short periods of leisure time on the internet at work help them to relieve boredom and stress and lead to greater job satisfaction, well-being and overall happiness (Eastin, Glynn, & Griffiths, 2007;Oravec, 2002;Reinecke, 2009;Stanton, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…One nationwide study in the United States found that fully 80% of computer-using employees report using the internet for personal use on the job (Garrett & Danziger, 2008). Such employees report that short periods of leisure time on the internet at work help them to relieve boredom and stress and lead to greater job satisfaction, well-being and overall happiness (Eastin, Glynn, & Griffiths, 2007;Oravec, 2002;Reinecke, 2009;Stanton, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers Belanger and Van Slyke, 2002;Block, 2001;Greenfield and Davis, 2002;Oravec, 2002;Stanton, 2002) argue that cyberloafing harms employers while others (Blanchard and Henle 2008;Case and Young, 2002;Coker, 2011;Coker, 2013;Greenfield and Davis, 2002;Lim, 2002;Malachowski, 2005;Mills et al, 2001) view that it enhances employee productivity. In this study, out of 20, 14 respondents rationalized that cyberloafing is beneficial for the secretaries of MWU whereas 6 respondents denied it.…”
Section: Rationalizing Cyberloafingmentioning
confidence: 99%
“…The advocates of cyberloafing at working place argue that the Internet provides a much needed positive diversion at work which can lead to creativity, flexibility, camaraderie, and foster a learning environment (Block, 2001;Belanger and Van Slyke, 2002;Greenfield and Davis, 2002;Oravec, 2002;Stanton, 2002;. Employees who engage in experimentation while cyberloafing may help develop important skills and knowledge which could make them more valuable to the organization (Sunoo, 1996;Belanger and Van Slyke, 2002;.…”
Section: Opportunities Of Cyberloafingmentioning
confidence: 99%
“…Additionally, clearly specified policies could lead to improving employee morale and attitudes [33,40,43], as well as an increase in their trust of the employer [3,46,51].…”
Section: Expectations Of Privacymentioning
confidence: 99%